Prevalence of perceived depression and anxiety among hypertensives attending imo specialist hospital owerri, Nigeria - Chikere Ifeanyi Casmir Ebirim; Ugonma Winnie Dozie; Somtochukwu Mercy Orji; Angela Juliet Uka-Okali; Uchenna Launa Iwumune; Queen KenechukwuDozie; Leo clinton Chukwu; Ekundayo Babajide Otuyelu; Chidiebere Peter Echieh; Uchenna Ewelike; Emmanuel Adeyemi Odumeru; Alvan Ifeanyi Okene; et al. (Archives of Depression and Anxiety - Peertechz Publications, 2020)
Background: Depression is a burdensome disease of global importance, and although prevalent, it is mostly undiagnosed in patients with hypertension. Anxiety is another significant factor associated with increased Blood Pressure and is an independent predictor of future hypertension. The aim of this study was to determine the prevalence of depression and anxiety among hypertensive's attending Imo Specialist Hospital Owerri, Nigeria. Methods: A hospital based cross sectional study was undertaken, utilizing systematic random sampling method in the recruitment of 334 respondents. Depression and anxiety was determined using a standard tool known as depression, anxiety, and stress scale-21 (DASS-21). The questionnaire was administered to the respondents by the researcher after an informed consent was obtained. Data were analyzed using SPSS version 21.  Results: A total of 334 respondents were recruited for the study comprising 190 (56.9%) females and 144 (43.1%) males. The Overall prevalence of depression and anxiety among the hypertensive patients was 77.8%. The result indicated that among the hypertensive's, 242 (72.5%) had both conditions of depressed and anxious, 74 (22.2%) were neither depressed nor anxious, 14 (4.1%) were anxious but not depressed while 4 (1.2%) were depressed but not anxious. Conclusion: A combination of hypertensive medications with psychotherapy and antidepressants can definitely help prevent severe attacks of High Blood Pressure. Hence, the study recommends the need for psychiatric evaluation, counseling, and support services for hypertensive patients as an important component for the management of hypertension especially at advanced stage.